The role of foreign-language communication in the international cooperation of law enforcement and military structures - Чорна, Анна Вадимівна (Київський інститут Національної гвардії України, 2025)
In the context of modern globalization, the issue of foreign-language communication in law enforcement and military structures is becoming particularly relevant, since international cooperation in the field of security and counteraction to transnational crime is becoming increasingly intensive and complex. Every day there is a need for the rapid exchange of operational information between states, the coordination of joint anti-terrorist measures, and the organization of training and practical operations in a multilingual environment. Under such conditions, the lack of sufficient foreignlanguage competence may lead to delays in response, misunderstandings during the execution of joint tasks, and even to critical mistakes that may threaten state security and international law and order
Keywords: Тези; foreign-language communication; international cooperation